Chloracne: From clinic to research - Qiang Ju; Kuochia Yang; Christos C. Zouboulis; Johannes Ring; Wenchieh Chen (Wolters Kluwer Medknow Publications, 2012)
Chloracne is the most sensitive and specific marker for a possible dioxin (2,3,7,8-tetrachlorodibenzo-p-dioxin) intoxication. It is clinically characterized by multiple acneiform comedone-like cystic eruptions mainly involving face in the malar, temporal, mandibular, auricular/retroauricular regions, and the genitalia, often occurring in age groups not typical for acne vulgaris. Histopathology is essential for a definite diagnosis, which exhibits atrophy or absence of sebaceous glands as well as infundibular dilatation or cystic formation of hair follicles, hyperplasia of epidermis, and hyperpigmentation of stratum corneum. The appearance of chloracne and its clinical severity does not correlate with the blood levels of dioxins. Pathogenesis of chloracne remains largely unclear. An "aryl hydrocarbon receptor"-mediated signaling pathway affecting the multipotent stem cells in the pilosebaceous units is probably the major molecular mechanism inducing chloracne. Chloracne is resistant to all the available treatment modalities used to treat acne. The aim of treatment is to lower or to eliminate the accumulated dioxins in the body at the very beginning of intoxication, e.g., by using dioxin-chelating substances such as synthetic dietary fat substitutes. The problem of dioxin contamination and its potential health hazards should be taken seriously in the wave of industrial globalization in the twenty-first century. Clinicians, especially dermatologists, are in the forefront of early diagnosis of dioxin intoxication.